2017
DOI: 10.3390/nu9070733
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Dietary Sources of Iron in Infants and Toddlers: Lessons from the FITS Study

Abstract: Iron deficiency (ID) affects 13.5% of 1–2 years old children in the US and may have a negative impact on neurodevelopment and behavior. Iron-fortified infant cereal is the primary non-heme iron source among infants aged 6–11.9 months. The objective of this study was to compare iron intakes of infant cereal users with non-users. Data from the Feeding Infants and Toddlers Study 2008 were used for this analysis. Based on a 24-h recall, children between the ages of 4–17.9 months were classified as ‘cereal users’ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 33 publications
(63 reference statements)
3
33
0
3
Order By: Relevance
“…Iron is a critical nutrient for infants and young children, and iron-fortified infant cereals, iron-fortified formula (for formula-fed infants), and iron-rich meats are important sources. FITS 2008 showed that infant cereal was the top food source of iron and 9 other vitamins and minerals for 6- to11.9-mo-olds ( 17 ). Among those infants who did not consume infant cereal, a substantial proportion (30–40%) had iron intakes below the Estimated Average Requirement compared with those infants who ate infant cereal (<8%).…”
Section: Discussionmentioning
confidence: 99%
“…Iron is a critical nutrient for infants and young children, and iron-fortified infant cereals, iron-fortified formula (for formula-fed infants), and iron-rich meats are important sources. FITS 2008 showed that infant cereal was the top food source of iron and 9 other vitamins and minerals for 6- to11.9-mo-olds ( 17 ). Among those infants who did not consume infant cereal, a substantial proportion (30–40%) had iron intakes below the Estimated Average Requirement compared with those infants who ate infant cereal (<8%).…”
Section: Discussionmentioning
confidence: 99%
“…Among older infants, fewer consumed iron-fortified baby cereal and iron-fortified formula ( 10 ) than reported in FITS 2008 ( 17 ). At the same time, few infants were fed iron-rich puréed baby meats.…”
Section: Key Findingsmentioning
confidence: 97%
“…Some suggest that during human evolutionary history this additional dietary iron may have come from pre-mastication of meat, a source of highly bioavailable heme iron [ 24 ]. Currently, the American Academy of Pediatrics encourages early introduction of pureed meat as a highly bioavailable source of heme iron [ 25 ], but intakes of meat by infants are low in the United States [ 26 ]. Canadian and Australian health authorities also recommend iron-rich complementary foods including meat ( Table 2 ).…”
Section: Iron Needs: Considerations During Pregnancy and Infancymentioning
confidence: 99%